NASA-TLX Assessment of Mental Workload in Manufacturing Industry - Hermansyah, Muhammad Saddam Akbar; Handayani, Naniek Utami (Spektrum Industri, 2022)
Mental workload assessment is essential for the optimal interaction of human system in the manufacturing industry. Manufacturing industry engaged in the construction, maintenance, and fabrication service. Performance of the worker will be lower if the higher workload. In the manufacturing industry are two type of workers that mainly involved in the fabrication process such as operator and welder. In This process was found several defects in the finished good which caused the company to suffer losses. Fatigue due to overtime work for seven days and a high mental workload. The aim of this study was to measure the mental workload in the manufacturing industry. In This study was performed on 10 worker in the operator and welder. Mental workload were assessed using NASA Task Load Index (NASA-TLX) and Fault Tree Analysis (FTA) tools. One operator workers and one of welders belonged to the heavy workload category. Finally, NASA-TLX was significantly higher for operator and welder. High mental workload in the manufacturing industry indicated the defection on mental workload. It is recommended to fixes are evaluating and updating rule work, system work, and existing SOP